Comparison on performance of two types permanent magnet generator - Misron, Norhisam; Masruni, Norafiza; M., Syafiq; Aris, Ishak; Wakiwaka, Hiroyuki; Nirei, Masami (2008)
This paper discusses the comparison on performance of a slot and a slot-less stator topologies of a single phase permanent magnet generator (PMG) driven by a petrol engine. The PMG was built especially for high speed performance. Generally, the technique used to examine the performance of the PMG is permeance analysis method (PAM). The theoretical analysis is verified by comparing the predicted and measured output power,resistance and inductance on a prototype of the PMG. The effect of armature reaction, copper losses and iron losses are also considered.